UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA MELALUI PENERAPAN MODEL PEMBELAJARAN INKUIRI PADA MATA KULIAH KONSEP DASAR IPA II DI PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR TAHUN AKADEMIK 2013/2014 - Mahmud Alpusari (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2014)
In line with the competency-based curriculum at the University of Riau, then efforts to improve learning in science courses Basic Concepts 2 put emphasis on understanding the concept of matter, which is based on students' learning activities through inquiry scientifik. Implementation of action research that consists of two cycles in PGSD JIP University of Riau, on the odd semester of the TA 2013/2014 with the third semester students study subjects by 55 students. Based on the research results , the lecture by applying the model of inquiry learning , increased student activity , where in the first cycle all activities except activities either category one and category two pretty while the first and second cycles of the four categorized well , while the activity of the second , third and sixth category five splendidly. While improving student learning of pre-tests with an average increased to 77.0 at 65.45 daily tests I and increased to 77.45 on the daily tests II, an increase from the first cycle of initial data points ranging from 11.55, while the data from the beginning of the second kesiklus increased average The average student score 12 points. Improved student learning outcomes in general possible because the learning model used inquiry learning so that learning becomes active which centered on the students by presenting a problem, then students are asked to carry out a simple experiment using equipment and tools, using data, prepare. reports, communicate the results of observations based on concepts and principles learned